2022
DOI: 10.1186/s13046-022-02345-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of carbonic anhydrases IX/XII by SLC-0111 boosts cisplatin effects in hampering head and neck squamous carcinoma cell growth and invasion

Abstract: Background Hypoxic tumor microenvironment (TME) contributes to the onset of many aspects of the cancer biology associated to the resistance to conventional therapies. Hypoxia is a common characteristic and negative prognostic factor in the head and neck squamous carcinomas (HNSCC) and is correlated with aggressive and invasive phenotype as well as with failure to chemo- and radio-therapies. The carbonic anhydrase isoenzymes IX and XII (CA IX/XII), regulators of extra and intracellular pH, are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Enzyme inhibition results confirmed that chemical manipulation of the linker and the tail could modulate the CA activity, despite the presence of a pan-CA inhibiting zinc binding group (sulphonamide). Cell-based data confirmed the relevant antiproliferative properties of this class of CAIs, the importance of the tumour-associated CAs for tumour growth and development, and their inhibition as a fruitful strategy to hamper these diseases, reinforcing previous data 37 , 38 on the significant antitumor effects of this class of CA inhibitors.…”
Section: Discussionsupporting
confidence: 77%
“…Enzyme inhibition results confirmed that chemical manipulation of the linker and the tail could modulate the CA activity, despite the presence of a pan-CA inhibiting zinc binding group (sulphonamide). Cell-based data confirmed the relevant antiproliferative properties of this class of CAIs, the importance of the tumour-associated CAs for tumour growth and development, and their inhibition as a fruitful strategy to hamper these diseases, reinforcing previous data 37 , 38 on the significant antitumor effects of this class of CA inhibitors.…”
Section: Discussionsupporting
confidence: 77%
“…This has been borne out in a number of in vitro and in vivo tumor models. Combining CAIX inhibitors with standard of care chemotherapy agents has been demonstrated to be significantly more efficacious than single agents alone [ 38 , 39 , 40 ]. Thus, combining the CAIX inhibitor, SLC-0111 with paclitaxel or with sunitinib in breast cancer [ 19 , 41 ], with temozolomide in pediatric and adult glioblastoma [ 42 ], with gemicitabine in pancreatic cancer [ 43 ], or an analog of SLC-0111, FC531, with cytarabine or Quizartinib in acute myeloblastic leukemia (AML) [ 44 ], results in greater inhibition of tumor growth and in significant increases in the survival of the tumor bearing mice.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…The ureido benzenesulfonamide SLC-0111 ( Figure 1 ) has been developed utilising the tail approach as the first-in-class h CA IX inhibitor which, for the management of metastatic hypoxic solid tumours, is currently being investigated within phase I/II clinical trials 3 , 23 , 24 . To date, numerous SLC-0111 analogues have been described with the prime aim to enhance potency and selectivity towards h CA IX exploiting bioisosteric replacement approach via replacement of the SLC-0111aryl tail by various sets of chemical scaffolds ( Figure 1 ) like benzofuran I 23 , thiazolo[3,2- a ]benzimidazole II 25 , triazine III 26 , thiazole IV , and thiadiazole V 27 .…”
Section: Introductionmentioning
confidence: 99%